Intoxicación experimental en caprinos por Baccharis coridifolia. - Vitulli Moya, G.; Aguirre Castro, Laura Sabrina; Colque Caro, Luis Adrián; Sandoval, Gabriela Virginia; Avellaneda Cáceres, Agustín; Micheloud, Juan Francisco (EEA Balcarce, INTA, 2022)
Poster